2020
DOI: 10.3389/fnbeh.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation Stress in Adolescence, but not Adulthood, Produces Hypersocial Behavior in Adult Male and Female C57BL/6J Mice

Abstract: Chronic stress during the developmental period of adolescence increases susceptibility to many neuropsychiatric diseases in adulthood, including anxiety, affective, and alcohol/substance use disorders. Preclinical rodent models of adolescent stress have produced varying results that are species, strain, sex, and laboratory-dependent. However, adolescent social isolation is a potent stressor in humans that has been reliably modeled in male rats, increasing adult anxiety-like and alcohol drinking behaviors, amon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 87 publications
2
33
3
Order By: Relevance
“…These effects are irreversible by resocialization [ 236 ], as observed in males but not in females [ 237 , 238 ]. SI reared rodents demonstrated despair-like behavior expressed as increased immobility time in the FST [ 76 , 239 ] that was reversed by chronic fluoxetine treatment [ 82 ], indicating a good predictive validity. SI-reared rats exhibited apathy-like behavior expressed as diminished grooming time and frequency in the splash test [ 75 ], mainly in males.…”
Section: Models Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects are irreversible by resocialization [ 236 ], as observed in males but not in females [ 237 , 238 ]. SI reared rodents demonstrated despair-like behavior expressed as increased immobility time in the FST [ 76 , 239 ] that was reversed by chronic fluoxetine treatment [ 82 ], indicating a good predictive validity. SI-reared rats exhibited apathy-like behavior expressed as diminished grooming time and frequency in the splash test [ 75 ], mainly in males.…”
Section: Models Of Depressionmentioning
confidence: 99%
“…SI-reared rats exhibited apathy-like behavior expressed as diminished grooming time and frequency in the splash test [ 75 ], mainly in males. In addition, some studies showed that SI-reared rats, either male or female, demonstrated increased adult social interaction [ 77 , 82 , 240 ].…”
Section: Models Of Depressionmentioning
confidence: 99%
“…One recent study found that aSI in C57BL/6J mice resulted in a hypersocial phenotype in males and females and an anxiolytic phenotype in females. Alcohol consumption was not affected in either of the sexes (Rivera-Irizarry et al, 2020 ).…”
Section: Negative Social Experiences and Drug Intakementioning
confidence: 99%
“…Reported results show that rewarding effects of social contact could be robustly observed in juvenile animals; however, the effect of social interaction is diminished or absent in early adulthood at the age of 8 weeks in male mice and at 11 weeks in females (Nardou et al, 2019). These results could be considered unexpected, as a lack of sCPP in adult mice would be at odds with other indices of social interaction preference in adult mice, such as the anxiogenic effects of isolation (Rivera-Irizarry et al, 2020) or communal nesting female behavior (Hayes, 2000).…”
Section: Introductionmentioning
confidence: 99%